2011
DOI: 10.1128/cvi.00542-10
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Threshold of Meningococcal Factor H Binding Protein Expression Is Required for Increased Breadth of Protective Antibodies Elicited by Native Outer Membrane Vesicle Vaccines

Abstract: Native outer membrane vesicles (NOMV) (not detergent treated), which are prepared from recombinant strains with attenuated endotoxin activity and overexpressed factor H binding protein (fHbp), elicited broad serum bactericidal antibody responses in mice. The amount of overexpressed fHbp required for optimal immunogenicity is not known. In this study we prepared NOMV vaccines from LpxL1 knockout (⌬LpxL1) mutants with penta-acylated lipooligosaccharide and attenuated endotoxin activity. The recombinant strains h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 43 publications
1
41
1
Order By: Relevance
“…Koeberling et al 17 showed that it is fully retained in lpxL1 nOMVs, and they further engineered strains for 3-to 10-fold higher expression by using plasmid constructs of either fHbp itself or its regulator. This higher fHbp expression turned out to be critical for getting an increased breadth of protective antibodies.…”
Section: Clinical Studies With Omv Vaccines Containing Non-toxic Lpsmentioning
confidence: 99%
“…Koeberling et al 17 showed that it is fully retained in lpxL1 nOMVs, and they further engineered strains for 3-to 10-fold higher expression by using plasmid constructs of either fHbp itself or its regulator. This higher fHbp expression turned out to be critical for getting an increased breadth of protective antibodies.…”
Section: Clinical Studies With Omv Vaccines Containing Non-toxic Lpsmentioning
confidence: 99%
“…Mice were challenged i.p. with approximately 50ϫ LD 50 of B. pseudomallei strain K96243. Two independent experiments were performed; survival was monitored up to day 14.…”
Section: Methodsmentioning
confidence: 99%
“…It may also be necessary to enrich the OMV cargo with virulence determinants specific to the intracellular stage of infection (44,45) or with antigens that induce strong T cell responses (46)(47)(48). A number of studies have shown that expression and delivery of homologous and heterologous antigens with OMVs are feasible (45,49,50). We previously showed that immunization with B. pseudomallei OMVs stimulates memory T cell responses and gamma interferon (IFN-␥) production (14).…”
Section: Figmentioning
confidence: 99%
“…Issues to be studied more carefully are duration of protection in various age groups, mucosal immunity and herd protection. Of particular note, a substantial difference in immunogenicity has been observed with recombinant fHbp versus the experimental formulations of native OMV vaccines where fHbp has been included as over-expressed vaccine antigen (NOMV-OEfHbp with 3-6 times the ordinary level found in wild type strains) [89][90][91]. The total amount of fHbp in the two formulations can be more than 100 times different, and the NOMV formulation induces better anti-fHbp immunity than the recombinant vaccine.…”
Section: Vaccines Against Meningococcal Disease; Status and Perspectivesmentioning
confidence: 99%